Calcium-fortified beverage supplementation on body composition in postmenopausal women - Haub, Mark D.; Simons, Tammy R.; Cook, Chad M.; Remig, Valentina M.; Al-Tamimi, Enas K.; Holcomb, Carol Ann (My University, 2010)
Background: We investigated the effects of a calcium-fortified beverage supplemented over 12 months on body composition in postmenopausal women (n = 37, age = 48–75 y). Methods: Body composition (total-body percent fat, %FatTB; abdominal percent fat, %FatAB) was measured with dual energy x-ray absorptiometry. After baseline assessments, subjects were randomly assigned to a free-living control group (CTL) or the supplement group (1,125 mg Ca++/ d, CAL). Dietary intake was assessed with 3-day diet records taken at baseline and 12 months (POST). Physical activity was measured using the Yale Physical Activity Survey. Results: At 12 months, the dietary calcium to protein ratio in the CAL group (32.3 ± 15.6 mg/g) was greater than the CTL group (15.2 ± 7.5 mg/g). There were no differences from baseline to POST between groups for changes in body weight (CAL = 0.1 ± 3.0 kg; CTL = 0.0 ± 2.9 kg), %FatTB (CAL = 0.0 ± 2.4%; CTL = 0.5 ± 5.4%), %FatAB (CAL = -0.4 ± 8.7%; CTL = 0.6 ± 8.7%), or fat mass (CAL = 1.3 ± 2.6 kg; CTL = 1.3 ± 2.7 kg). Conclusion: These results indicate that increasing the calcium to protein ratio over two-fold by consuming a calcium-fortified beverage for 12 months did not decrease body weight, body fat, or abdominal fat composition in postmenopausal women.
Keywords: Obesity; Body fat; Supplement; Obese; Diet; Juice